2021
DOI: 10.1093/bib/bbab485
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics integration-based molecular characterizations of COVID-19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), rapidly became a global health challenge, leading to unprecedented social and economic consequences. The mechanisms behind the pathogenesis of SARS-CoV-2 are both unique and complex. Omics-scale studies are emerging rapidly and offer a tremendous potential to unravel the puzzle of SARS-CoV-2 pathobiology, as well as moving forward with diagnostics, potential drug targets, risk stratific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…The enhancement of Nrf2 transcription with sulforaphane or melatonin could benefit patients with “LONG COVID” (Post-Acute Sequelae of SARS-CoV-2 or Post-COVID-Syndrome), a significant proportion (approximately 40%) of individuals with COVID-19 experiencing a variety of symptoms (loss of smell and/or taste, fatigue, cough, aching pain, “brain fog,” insomnia, shortness of breath, and tachycardia) after 12 weeks ( Jarrott et al, 2022 ; Ordonez et al, 2022 ). Multi-omics studies revealed that SARS-CoV-2 infection provokes significant changes in numerous metabolites including those impacting on virus propagation (one-carbon metabolism) and GSH synthesis (amino acids glutamic acid, cysteine and glycine) that could be used as early prognosis biomarkers in COVID-19 at diagnose to predict severe COVID-19 and “LONG COVID” ( Doğan et al, 2021 ; Li C.-X. et al, 2022 ; Perła-Kaján and Jakubowski, 2022 ; Valdés et al, 2022 ).…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
“…The enhancement of Nrf2 transcription with sulforaphane or melatonin could benefit patients with “LONG COVID” (Post-Acute Sequelae of SARS-CoV-2 or Post-COVID-Syndrome), a significant proportion (approximately 40%) of individuals with COVID-19 experiencing a variety of symptoms (loss of smell and/or taste, fatigue, cough, aching pain, “brain fog,” insomnia, shortness of breath, and tachycardia) after 12 weeks ( Jarrott et al, 2022 ; Ordonez et al, 2022 ). Multi-omics studies revealed that SARS-CoV-2 infection provokes significant changes in numerous metabolites including those impacting on virus propagation (one-carbon metabolism) and GSH synthesis (amino acids glutamic acid, cysteine and glycine) that could be used as early prognosis biomarkers in COVID-19 at diagnose to predict severe COVID-19 and “LONG COVID” ( Doğan et al, 2021 ; Li C.-X. et al, 2022 ; Perła-Kaján and Jakubowski, 2022 ; Valdés et al, 2022 ).…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
“…Since viruses are able to modulate lipid synthesis and signaling into the host cell to produce lipids for their envelopes by creating a lipid micro-environment ideal for replication, the lipid dysregulation is suggested as a drug target to prevent coronavirus infection [ 28 ]. Furthermore, considering the high heterogeneity of the clinical manifestations of COVID-19, thus suggesting the involvement of diverse pathophysiological processes [ 29 ], multiomics approaches and data integration analyses may result as a winning choice, contributing to a better understanding of the molecular biology of SARS-CoV-2 at every level of complexity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, severe COVID-19associated hyperinflammatory syndromes have been reported that they originate from a host innate immune response (37). Studies of transcriptome, proteomic, and epigenomics have revealed a wide range of functional impairments, including marked neutrophil hyperactivation symptoms in severe COVID-19 (38)(39)(40)(41). Collectively, COVID-19 caused by SARS-CoV-2 is associated with a failure of innate and adaptive immune system regulation due to changes in other immune cells associated with a decrease in adaptive T cells.…”
Section: Dysregulated Immune Response In Covid-19mentioning
confidence: 99%